2015
DOI: 10.1002/ange.201509346
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Solid‐Phase Route to Renewable Aromatic Chemicals from Biobased Furanics

Abstract: Renewable aromatics can be conveniently synthesized from furanics by introducing an intermediate hydrogenation step in the Diels-Alder (DA) aromatization route,to effectively blockr etro-DAa ctivity.A romatization of the hydrogenated DA adducts requires tandem catalysis,u sing am etal-based dehydrogenation catalyst and solid acid dehydration catalyst in toluene.H erein it is demonstrated that the hydrogenated DA adducts can instead be conveniently converted into renewable aromatics with up to 80 %s electivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In the reaction of DMF and maleic anhydride, the full decarboxylation was achieved with 3 % yield of PX. Three products (i.e., PX, 2,5‐DMBA and dimethylphthalic anhydride) obtained in one step at 50 °C in this reaction were identical to those obtained in a solid phase reaction at 200 °C . As the dehydration and decarboxylation of the Diels–Alder adduct of DMF and maleic anhydride hardly occur in traditional solvents because of the retro Diels–Alder reaction, it can be concluded that the Diels–Alder adduct was stabilized and the retro Diels–Alder reaction was prevented through the use of an ionic liquid.…”
Section: Resultssupporting
confidence: 51%
“…In the reaction of DMF and maleic anhydride, the full decarboxylation was achieved with 3 % yield of PX. Three products (i.e., PX, 2,5‐DMBA and dimethylphthalic anhydride) obtained in one step at 50 °C in this reaction were identical to those obtained in a solid phase reaction at 200 °C . As the dehydration and decarboxylation of the Diels–Alder adduct of DMF and maleic anhydride hardly occur in traditional solvents because of the retro Diels–Alder reaction, it can be concluded that the Diels–Alder adduct was stabilized and the retro Diels–Alder reaction was prevented through the use of an ionic liquid.…”
Section: Resultssupporting
confidence: 51%
“…In contrast, 2-methylfuran and 2,5-dimethylfuran readily react with maleic anhydride to yield thermally labile unsaturated D-A adducts, which can then be hydrogenated or dehydrated to make tricyclic or phthalic anhydrides, respectively, with a targeted number of methyl substituents (Fig. 1b ) 16 18 .…”
Section: Resultsmentioning
confidence: 99%
“…[1] Notable examples include the synthesis of: p-xylene from dimethylfuran and ethylene, [3][4][5][6][7][8][9][10][11][12][13][14] acrylic acid [15,16] or acrolein; [17] benzene/toluene from furan and ethylene/propylene; [18] and (substituted) phthalic anhydride from (substituted) furan and maleic anhydride. [19][20][21] In general, there are two key considerations that determine how successful these reactions are: 1) the kinetic and thermodynamic efficiency of the DA reaction and 2) the ease with which the resulting DA cycloadduct can be aromatised. Either one can make or break the process and the outcome depends heavily on the diene/dienophile combination used.…”
mentioning
confidence: 99%